The Truth Campaign And The War of Ideas - Favat, Pete; Price, Bryan C.
The importance of the war of ideas between the United States and jihadist organizations has been well understood by our adversaries since 9/11. In the early days of the long war, Ayman al-Zawahari, long-time deputy to Usama bin Laden and al-Qa`ida s current leader, declared that more than half of this battle is taking place in the battlefield of the media. We are in a media battle in a race for the hearts and minds of our umma.
Keywords: Guerra de ideas